CAPAIAN PELAYANAN KESEHATAN HIPERTENSI (Studi Observasi di Puskesmas Wonogiri 1) - Handayani, sri; Siti Mawarni (Jurnal Keperawatan GSH, 2024)
Health is a basic need for every human being. Puskesmas is a health service facility that aims to provide first-level public health efforts and individual care, with an emphasis on services for the wider community in order to achieve optimal health, without neglecting the quality of service to individuals. Hypertension health services are one of the services available at the Community Health Center. Hypertension is a disease characterized by long-term increases in blood pressure. Hypertension is also called the silent killer because hypertension is a hidden killer whose initial cause is unknown or has no symptoms at all. The method used is observational with the aim of finding out the targets for achieving hypertension health services at the Wonogiri Community Health Center 1. Results of achieving hypertension health services at the Wonogiri Community Health Center 1 the first quarter was 2,764 (15.35%), the second quarter was 3,174 achievements (18%), the third quarter was 2,082 (12%), the fourth quarter was 3,246 (18%). Total achievement in 2022 is 11,266 or 62.57%. Based on this data, it shows that the target for achieving hypertension health services at the Wonogiri 1 Community Health Center in 2022 is still 37.43% short. Keywords: Hypertension; Health services